Flutter Framework Implementation for Over Current Relay and Ground Fault Relay Setting Applications in 20 kV Distribution Systems - Sartika, Nike; Maulidan, Muhammad Akmal; Mulyana, Edi (Jurnal Pendidikan Multimedia (Edsence), 2024)
In the distribution system, there are several faults such as blackouts due to errors in the coordination of the protection relay. To minimize excessive damage to the electrical system, components such as over current relays (OCR) are needed to overcome inter-phase faults and ground fault relays (GFR) to overcome phase-to-ground faults. The setting process that has been carried out so far is still ineffective, so a system is needed to simplify the setting process. Flutter is a development framework from Google that can release applications in the form of Android or iOS. This study aims to simplify the OCR and GFR setting process using a mobile application. Application development uses the waterfall method. The test results consisting of blackbox alpha, beta and manual calculations show that this application is running according to the expected functionality. In addition, the results of the settings that have been done are the OCR setting current of 400 A in zone 1 and 300 A in zone 2 with a Time Multiplier Setting (TMS) value of 0.2 in zone 1 and 0.05 in zone 2. While the GFR setting current is 80 A in zone 1 and 60 A in zone 2 with a TMS value of 0.175 in zone 1 and 0.05 in zone 2. From these setting values, the OCR time difference (Δt) value is then obtained around 0.6 seconds and 0.8 seconds for GFR. This shows that the OCR and GFR are in good condition.